ANALISIS KESALAHAN EJAAN BAHASA INDONESIA DALAM ARTIKEL ILMIAH MAHASISWA UNIVERSITAS NEGERI MEDAN - Adzkia Rizkianisa Awira Siregar; Marshanda Manurung; Mika Debora Hutasoit; Nurul Dwi Dara Auliya; Khoirun Nisa; Vatrick Tarigan; Elly Prihasti (STKIP Subang, 2026)
This study aims to analyze Indonesian spelling errors in scientific articles written by students of Universitas Negeri Medan and to examine the conformity of the articles’ writing structure with scientific writing standards. The research employed a qualitative descriptive method using documentation techniques. The data source consisted of 11 scientific articles written by students of the Indonesian Language and Literature Education Study Program, Regular A Class of 2024, Universitas Negeri Medan. Data were collected through reading and note-taking techniques and analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The results revealed various spelling errors in the aspects of letter usage, word writing, punctuation, and loanword writing. The most common errors included incorrect capitalization, typographical mistakes, nonstandard word usage, improper punctuation, and inconsistencies in writing foreign terms. In addition, several weaknesses were found in the systematic structure of scientific articles, particularly in titles, author identities, abstracts, conclusions, and references. Nevertheless, most articles had generally followed the standard structure of scientific writing. These findings indicate that students’ understanding and application of Indonesian spelling rules and scientific writing conventions still need improvement to enhance the quality of academic writing.